Penerapan Fuzzy TOPSIS dalam Penentuan Lokasi Kawasan Pengembangan Rantai Pasok Bioenergi Kelapa Sawit - Petir Papilo; Taufik Djatna; Yandra Arkeman; Marimin Marimin (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2018)
This study aims to obtain the best location of the target area of agro-industrial development of bioenergy in the supply chain. Through a systems approach, using fuzzy TOPSIS, an analysis of various key criteria was conducted, including availability of raw materials, land conditions and prices, the ease of access to transportation, the distance to the city center, the availability of labor at the target location, availability of infrastructure – such as water and electricity, the use of the location and orientation of multiplier effect. Based on the results of the analysis that has been done, from the five areas being targeted for locations of bioenergy agro-industry development in the province of Riau, including Industrial Area Kuala Enok; Palm Oil Region in Rokan Hulu; Pelintung Dumai Industrial Area; Palm Oil Region in Bagan Batu Rokan Hilir and Teknopolitan Region in Pelalawan, the one that has been voted the best location is Pelintung Dumai Industrial Area. ABSTRAKPenelitian ini bertujuan untuk memperoleh lokasi terbaik yang menjadi target kawasan pengembangan agroindustri bioenergi dalam satu mata rantai pasokan. Melalui pendekatan sistem, dengan menggunakan metode fuzzy TOPSIS, dilakukan analisis terhadap berbagai kriteria penting diantaranya ketersediaan bahan baku, kondisi lahan dan harga, kemudahan akses transportasi, jarak lokasi dengan pusat kota, ketersediaan tenaga kerja pada lokasi sasaran, ketersediaan infrastruktur seperti air dan listrik, orientasi pemanfaatan lokasi serta multiflier effect. Berdasarakan hasil analisis yang telah dilakukan, dari lima target kawasan yang menjadi sasaran lokasi pengembangan agroindustri bioenergi di Provinsi Riau, diantaranya Kawasan Industri Kuala Enok, Kawasan Perkebunan Kelapa Sawit di Rokan Hulu, Kawasan Industri Pelintung Dumai, Kawasan Perkebunan Kelapa Sawit di Bagan Batu Rokan Hilir dan Kawasan Teknopolitan di Kabupaten Pelalawan, telah terpilih lokasi terbaik, yakni di Kawasan Industri Pelintung Dumai